Environmental Sustainability of Nickel Waste Utilization in Porous Asphalt: Toward Green and Circular Road Infrastructure - Fatmeriany, Fatmeriany; Desi, Natsar; Chaerul, Muhammad; Harun, A. Muh. Yusuf; Erniati, Erniati; Marzuki, Ismail; Gusty, Sri (Journal La Lifesci, 2025)
The rapid growth of road infrastructure in Indonesia has increased the demand of construction materials and at the same time, intensified environmental issues. The study explores the potential application of nickel waste- which is a byproduct readily available to Indonesia in the smelting of nickel- as a partial replacement to coarse aggregate in porous asphalt mixtures. The research not only assesses the technical performance but also the environmental impact of the nickel waste substitution which can be regarded as a contribution to the literature on sustainable management of the construction process and the circular economy. Key parameters such as stability, flow, void content and the Marshall Quotient were tested in the laboratory and were evaluated as per the Bina Marga and SNI requirements. The results refer to the fact that nickel waste may meet a number of technical requirements, reaching an ideal concentration of asphalt into 5.5 0-100 that, at the same time, can provide waste minimization and possible cost-saving benefits. However, due to the fact that nickel slag contains heavy metals, it requires the use of strong environmental risk management, such as leaching control and stabilization technologies. These findings indicate that the use of nickel waste is more than a technical innovation; it is a strategic direction of the ability to become resource-efficient, symbiotic in the industrial industry, and to govern the operation of infrastructure in a sustainable manner. Placing industrial waste in a new category as productive input, this research sheds some light on how policy can be changed, how to innovate in procurements, and how government, industry, and academia can collaborate. The study concludes that the addition of nickel waste to the porous asphalt mixtures could help improve the performance of roads, reduce environmental ecological impacts, and promote the green infrastructure agenda in Indonesia, assuming that there are regulatory protections and a systematic environmental check-up.